Barriers to home bowel screening test in South Asians in the UK. (30th September 2020) - Smith, L; Howcutt, S; Saini, P; Brett, J; Henshall, C; Watson, E
Abstract: Background: Bowel cancer is common and accounts for 10% of all cancer mortality. Early detection significantly reduces mortality. In the UK, the NHS Bowel Cancer Screening Programme invites adults aged 60-74 years to carry out a home screening test biennially. The national target for test completion is 60%; completion is substantially lower (∼30%) amongst South Asian populations. Our aim was to develop a community-based intervention to increase completion of the home bowel screening test in South Asians. Methods: Multi-methods comprising two stages: 1) group and individual interviews with South Asians aged 50-74 years purposively sampled from community groups for maximum variation. Semi-structured interviews based on the Theoretical Domains Framework (TDF) investigated determinants of bowel screening completion. Interviews were recorded, transcribed, and analysed using framework analysis and findings mapped onto the COM-B Behaviour Change Wheel; 2) Co-production of intervention during two workshops with key stakeholders and target population. Results: To-date 25 adults recruited of Indian, Pakistani and Bangladeshi ethnicity with variation in age, gender, first language, faith, and compliance with bowel screening. Key barriers and TDF domains that they mapped to were: - lack of knowledge about bowel cancer and screening; lack of language, literacy and physical ability (skills) to carry out the home test; confidence to carry it out correctly (belief about capabilities); appropriate space and time to carry out the test (environmental context and resources); putting off undertaking the test (memory attention and decision processes); risk perception and fear of cancer (emotions). Enablers were: social influences from peers; goals and motivations. Conclusions: Early results suggest an intervention comprising education, persuasion, modelling and enablement functions could increase completion of the home test. Key messages: Community engagement and working with community leaders enhanced the success of recruitment. The TDF was a useful framework for identifying barriers to home bowel screening test by South Asians in the South East of England.